2017
DOI: 10.1111/jfpe.12567
|View full text |Cite
|
Sign up to set email alerts
|

Effects of variable steaming on chemical composition, starch characteristics, and glycemic index of basmati (Pusa Basmati 1121) rice

Abstract: Effects of variable steaming on important quality characteristics of Pusa Basamti 1121 rice were evaluated in the study. Pre‐soaked (at 65°C for 345 min) paddy was steamed at variable steaming consisted of 4 pressure levels (0–1.5 kg/cm2) and 5 steaming times (5–25 min). Steaming affected rice quality characteristics significantly (α = 0.05). It increased head rice yield by 12%. Starch, amylose, Am/Ap ratio, crude protein, crude fats, crude fibers, and ash contents of steamed rice varied from 63.34 to 68.24%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
3
14
0
Order By: Relevance
“…The brown glutinous rice which was soaked at 90 0 C and steamed until 100% gelatinization has the lowest GI value (61.32 or 7.72% reduction). This is a similar value when compared to the previous study of Kale et al, 17 , which investigated the effect of parboiling on GI of Basmati rice, the result showed that there is 6-8% GI value reduction. During cooking, the heat, the amount of water, and the cooking time affected the GI of food.…”
Section: Rs and In Vitro Starch Digestibilitysupporting
confidence: 87%
See 1 more Smart Citation
“…The brown glutinous rice which was soaked at 90 0 C and steamed until 100% gelatinization has the lowest GI value (61.32 or 7.72% reduction). This is a similar value when compared to the previous study of Kale et al, 17 , which investigated the effect of parboiling on GI of Basmati rice, the result showed that there is 6-8% GI value reduction. During cooking, the heat, the amount of water, and the cooking time affected the GI of food.…”
Section: Rs and In Vitro Starch Digestibilitysupporting
confidence: 87%
“…Normally, rice with higher levels of RS has a lower GI value. 16 The effects of parboiling techniques on GI have been investigated by Kale et al, 17 The results showed that parboiling at temperatures higher than 60 0 C could decrease the GI from 58 to 54. This was due to amylose-lipid complexes being formed and digested more slowly in the small intestine.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the previous work has also reported strong negative correlation of RS and GI in rice cultivars even after cooking 44 where as high amylose content rice cultivars have been reported to have low GI 24 , 45 . GI of Pusa Basmati 1121 has been reported as 58.41% which has been shown to reduce by steaming of the paddy or by different cooking treatments 46 , 47 . As compared to basmati; the land races like, ‘Kataribhog’, ‘A-1-1’, ‘Dubarikomal’, ‘KNS-2B-S1’, ‘TPUR-B-1 (IET 28104)’ etc.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, parboiling may result in increased resistant starch fraction and low glycemic index (GI) which are health-promoting. [19] Traditionally to make parboiled rice, paddy is soaked in water for 48 h followed by steaming and drying. [3] As the global food index is taking a step forward from food security to food safety, innovations and improvements in the parboiling process are becoming a subject of research interest.…”
Section: Introductionmentioning
confidence: 99%